Comparison of the gut microbiota composition between asymptomatic and diseased Epinephelus moara ♀ × Epinephelus lanceolatus ♂ with nervous necrosis virus infection. (8th October 2021) - Wang, Linna; Tian, Yongsheng; Li, Zhentong; Li, Ziqi; Chen, Shuai; Li, Linlin; Li, Wensheng; Wang, Qingbin; Lin, Haowei; Li, Bo
Abstract: Yunlong grouper ( Epinephelus moara ♀ × Epinephelus lanceolatus ♂ ) is a new hybrid grouper with high economic value because it has shown some superiority in terms of growth, temperature tolerance, deformity resistance and some nutritional indicators compared with its parents. Currently, the aquaculture industry of grouper is plagued by viral diseases, and there is still no effective control method. Gut microbiomes have a significant impact on the digestion, immunity, metabolism, health and behaviours. In this study, 16S rRNA gene sequencing was performed to characterize the gut microbiota of yunlong grouper, and the differences in community composition between the asymptomatic and diseased fish naturally infected with nervous necrosis virus (NNV) were compared. A total of 3262 OTUs with ≥97% sequence similarity of 31 bacterial phyla were identified. In all grouper samples, the most abundant phylum was Proteobacteria and the most abundant genus was Blastopirellula, the predicted functions in gut bacteria were mainly involved with metabolism. There were no significant differences between two groups of yunlong grouper in α‐diversity analysis. Specific bacterial taxa difference for each group from the phyla to the genus level was identified using LEfSe analysis. This is the first report of comparison of the gut microbiota between asymptomatic and diseased yunlong grouper under NNV infection. These findings provide an understanding about the interaction between intestinal microbiota and host under NNV infection, and provide targets for future probiotics screening.